Influence of Working Conditions on Turnover Intentions of Secondary School Teachers in Meru County - Ekabu, Peter Kalunge; M.Kalai, Jeremiah; Nyagah, Grace (European Scientific Journal, ESJ, 2018)
The objective of this study was to examine the relationship between working conditions and teacher turnover intentions in public secondary schools in Meru County, Kenya. The study used a descriptive survey design with both quantitative and qualitative approaches in data collection and analysis. A total of 520 respondents were involved in the study that included 503 secondary school teachers, 15 principals and 2 staffing officers. Teachers working conditions were examined to determine their relationship with turnover intentions. Data obtained from teachers’ questionnaires were analyzed quantitatively using SPSS version 21.Hypotheses were tested using Pearson product moment correlation coefficient and chi-square goodness of fit at 95%, p<0.05. The result of product moment correlation analysis indicated that the independent variable, working conditions (r= -0.488, p<0.001) have a negative and an inverse relationship with the independent variable, turnover intention. These results were agreed with the results of Chi-square analysis for both the independent variable which showed a significant relationship between working conditions and turnover intentions of secondary school teachers in Meru County. The results therefore established that teachers’ motivation in secondary schools in Meru County is low due to poor working conditions and the education system appears to be staffed with teachers with poor morale and low levels of commitment to their jobs leading to high turnover intentions. The study recommends the various Boards of Management and other education stakeholders at the national and county government levels consider issues of teachers working conditions as an essential element in the motivating and reducing turnover intentions hence retention in teaching service.